Development of Optimization Methodology for Short Range Air-to-Air Missile - Romie Oktovianus Bura; Yudki Utama; Muhammad Farraz (Universitas Lampung, 2018)
This paper illustrates the development and the use of conceptual sizing tools integrated with optimization tools. The conceptual sizing tool is based on empirical and simple analytical calculation that simple and robust enough for wide range of inputs. The genetic algorithm optimization method then used to explore the global optimum for given variables. System response analysis is conducted to gain insight about the sensitivity of objective function because of design variables.